The Inception of SKB on Ahmadiyya: From State of Power to State of Law - Mochamad Sodik; Gufron Gufron; B.J. Sujibto (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
The product of the law on Ahmadiyya, known as the SKB (Surat Keputusan Bersama) or Joint Ministerial Decree, bans them from conducting religious activities, has provoked a polemic and controversy. This article examines the socio-political process of the SKB and criticizes the essence of the state of the law by proposing the concept of limitation of power. Ahmadiyya adherents in Manislor, Kuningan, have become role models in responding to the dynamics of the SKB. Using a qualitative approach to understand the local voices and experiences deeply, the data were based on fieldwork and collected through observations, interviews, and documentation. This article found that (1) the SKB is a controversial political product since the birth of SKB was influenced by various political powers consisting of internal and external parties; (2) the current social situation of Ahmadiyya adherents in Manislor who fervidly initiated to overcome the conflict affected the dynamics of social actors in supporting the process of social integration within society; and (3) the limitation of the power of the government and state apparatus is crucial to avoid abuse of power in dealing with minorities. The limitation of local and national government power is required to obey the law, human rights, and other noble values originating from religious, moral, and ethical norms.